THE OPTIMALIZATION GARBAGE COLLECTION ROUTE BY USING CLARKE SAVING HEURISTIC METHOD IN MEDAN - Daulay, Maeyra Sapani; Cipta, Hendra (UIN Sumatera Utara, 2023)
Waste is a classic problrm that occurs in metropolis such as Medan. As a city of trade and industry, the waste generated in Medan city is increasing every day. This research was made based on the problems that exist in Medan Marelan Sub-district. The problem of waste distribution in Medan Marelan does not yet have a fixed route and runs two routes or two rounds every day so that waste transportation is not optimal which results in piles of garbage at several points that are missed and ineffective time. Based on these problems, this research was made using the Clarke and Wright Saving Heuristic method. The purpose of this study is to determine the optimal waste transportation route for waste distribution so as to minimize distribution costs. From the processing, the route that will be obtained can be determined by two methods, namely nearest neighbor and farthers insertion. From the observations of the two methods used, the total distance on each route is different. For example, on the first Typer Truck route, the Farthest Insert Method is 34.126 km and the Nearest Neighbor Method is 32.595 km with the required fuel of 6.8 liters and 6.5 liters. The second Typer Truck Farthest Insert Method is 13.275 km and the Nearest Neighbor Method is 13.506 km with 2.65 liters and 2.7 liters of fuel. And the third Typer Truck Farthest Insert Method is 13.075 km and Nearest Neighbor Method is 13.225 km with 2.6 Liters and 2.64 Liters offuel.